2020
DOI: 10.1029/2020je006429
|View full text |Cite
|
Sign up to set email alerts
|

Meter‐Scale Topographic Roughness of the Moon: The Effect of Small Impact Craters

Abstract: High‐resolution digital terrain models (DTMs) generated from the Lunar Reconnaissance Orbiter Camera (LROC) Narrow Angle Cameras (NACs) provide an opportunity to study surface roughness of the Moon at meter scale. In this study, we mapped and investigated meter‐scale topographic roughness over 462 regions of the Moon using NAC DTMs. Our results show that, at meter to hectometer scales, there are obvious differences in median bidirectional slope, root‐mean‐square (RMS) height, and median absolute slope between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(72 citation statements)
references
References 51 publications
1
70
1
Order By: Relevance
“…Examination in the optical image (Figure 7a) shows that there are degraded craters with diameter of ∼70–200 m. According to their morphologic prominence, they can be classified as moderately degraded craters of morphologic type B, with a typical depth/diameter ratio of 0.1. A recent study shows that depth/diameter ratio of small fresh craters at this large is ∼0.13–0.16 (Cai & Fa, 2020). If the difference in crater depth between fresh and degraded craters is regarded as regolith thickness, then the thickness of regolith can be estimated as 2–12 m. Therefore, our estimation of ∼1.5 m to >8 m regolith thickness at the CE‐5 landing region is reasonable.…”
Section: Discussionmentioning
confidence: 87%
“…Examination in the optical image (Figure 7a) shows that there are degraded craters with diameter of ∼70–200 m. According to their morphologic prominence, they can be classified as moderately degraded craters of morphologic type B, with a typical depth/diameter ratio of 0.1. A recent study shows that depth/diameter ratio of small fresh craters at this large is ∼0.13–0.16 (Cai & Fa, 2020). If the difference in crater depth between fresh and degraded craters is regarded as regolith thickness, then the thickness of regolith can be estimated as 2–12 m. Therefore, our estimation of ∼1.5 m to >8 m regolith thickness at the CE‐5 landing region is reasonable.…”
Section: Discussionmentioning
confidence: 87%
“…The weak heterogeneity of the lunar regolith does not seriously influence the imaging and inversion [24,29,30] because it is too weak compared with the reflections from the ejecta. However, further study of these weak heterogeneous characteristics would be helpful in revealing the process of lunar regolith formation, particularly to the most recent stage of local small impacts [31]. Of course, long-distance heavy bombardments may also convey an amount of small-particle ejecta and contribute to such an ultra-thick layer of fine regolith on the far side of the Moon [32].…”
Section: Introductionmentioning
confidence: 99%
“…For hectometer-scale roughness analysis, Kreslavsky et al [13] considered that no significant roughness differences existed between maria and highlands. Cai and Fa [14] showed that hectometer-scale roughness textures were mainly controlled by small and degraded impact craters. The proposed roughness maps indicate that more complex geomorphological features cause the higher roughness textural changes.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the multi-scale roughness properties of lunar surface are discussed at meter-scales, hectometer-scales, and kilometer-scales. The meter-scale roughness parameters of the lunar surface are mainly controlled by small and degraded impact craters [14]. Hectometer-scale roughness is related to the regolith accumulation and modification processes, while kilometer-scale roughness reflects major geological events [13].…”
Section: • B Window-based Roughness Quantificationmentioning
confidence: 99%
See 1 more Smart Citation